Book Review of Going Solo: The Extraordinary Rise and Surprising Appeal of Living Alone - Orsolya Kolozsvari (Journal of Public and Professional Sociology)
Review of Going Solo: The Extraordinary Rise and Surprising Appeal of Living Alone, by Eric Klinenberg. New York: Penguin Books, 2013.